TANTANGAN PENGEMBANGAN USAHA PANGAN OLAHAN ORGANIK: KREATIVITAS DAN INOVASI (STUDI PADA KELOMPOK WANITA TANI VIGUR ORGANIK KOTA MALANG) - Muljaningsih Sri (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT This study aims to find out problems in developing business faced by Vigur Organik Female farmers Group (KWT). KWT is micro, small and medium enterprises (UMKM) that develops Processed Organic Food (POO) in Malang.  Method of problem solving used is root cause analysis - cause is fishbone diagram.  Problem is an obstacle which becomes challenges for KWT in the business development of POO.  The main problem faced by KTW Vigur Organic's member is capitalization.  Supporting causes of this problem are among others, lack of land to grow organic plants, community's interest to start POO business is low, raw material is limited, methods used is still traditional and there is no vacuum fraying owned by KWT Vigur Organik.   However, KWT Vigur Organik has high spirit to perform trial phase and creativity to result POO since it does not necessarily obtain raw material that meets organic criterion.  That creativity produces product innovation.  The featured products of KWT Vigur Organik are soy sauce for people with autism and kerupuk puli (rice crackers).  It is indeed that those products uses raw material which has national standard for organic food.   This can be concluded that the way to develop POO business is through creativity and product innovation.   Suggestion to develop this kind of business is KWT needs to carry out innovation in marketing.  Limit of this study is the researcher do not know yet the strategy performed by KWT Vigur Organik for market stabilization in the era of global and digital.